Efektivitas Teknik Progesive Muscle Relaxtation, Dengan Progesive Muscle Relaxtation Dan Dzikir Anfas Terhadap Kecemasan - Annas Annas; Kabul Wibowo (ILIN Institute Makassar, 2019)
This Study aoims to deremine the effect of PMR ( Progresive Muscle Relaxtation) therapy, PMR (Progesive Muscle Relaxtation) and Anfas Remembrance to reduce PAPP Khodijah students' anxiety, and to find out the difference in PMR, PMR and Dzikir Anfas Therapy which is more effective than the two therapies reduce anxiety levels. The method used is by using the Quasi experimental research design pretest and post test with control group. With Progressive Muscle Relaxation therapy intervention with Progressive Muscle Relaxation and Anfas dhikr as a control group. Each group consisted of 5 participants, within one week the research was conducted at PAPP Khodijah. The results of the study obtained Based on the results of the Mann Whitney U test on the gain score changes in the value of anxiety the progressive group muscle relaxtation, PMR and Anfas Dhikr were Z = -623, P = 0.548 (P?0.05). This explains that both PMR and PMR groups and Dzikir Anfaz did not have a significant difference.